Conditions de vie et expérience doctorale en France - Marion Tavant; Julien Berthaud; Jean-François Giret (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
As higher education undergoes transformation and the professionalization of the PhD gives rise to new profiles of young researchers, this article aims to explore the hypothesis of a significant segmentation among doctoral experiences. Doctoral satisfaction and mental health are examined in relation to the living conditions of PhD students, taking into account the mode of thesis funding and proposing six PhD student profiles. The empirical data, based on the OVE’s “2020 Student Living Conditions” survey, benefits from a sample of 636 university doctoral students. The profiles of PhD students appear heterogeneous, with some facing precarious conditions. The results, obtained through logistic regressions, generally reveal disparities among PhD student regarding their doctoral experiences (overall doctoral satisfaction and mental health).